La renta señorial de la Orden de San Juan en Castilla durante los siglos XII y XIII - Barquero Goñi, Carlos (Espacio Tiempo y Forma. Serie III, Historia Medieval, 2016)
La Orden de San Juan obtuvo muchos recursos de sus dominios en Castilla durante los siglos XII y XIII. Sus fuentes de renta eran las contribuciones habituales en el régimen señorial durante la Edad Media. Sin embargo, el principal ingreso era una parte del diezmo eclesiástico que la Orden percibía en sus señoríos. The Order of Saint John collected significant resources from their domains in Castile during the twelfth and thirteenth centuries. Their sources of income were the usual contributions of the manorial system during the Middle Ages. Nevertheless, their main source of income was a fraction of the ecclesiastical tithe that the order perceived in their lordships.